2020
DOI: 10.1093/jat/bkaa113
|View full text |Cite
|
Sign up to set email alerts
|

Eutylone Intoxications—An Emerging Synthetic Stimulant in Forensic Investigations

Abstract: Synthetic stimulants are the largest class of novel psychoactive substances (NPS) identified each year by forensic laboratories internationally. While hundreds of these drugs appear in drug powders, only a few proliferate in use among forensically relevant populations, eventually emerging in postmortem and clinical investigations. Beta-keto-methylenedioxyamphetamines (i.e., NPS with names ending in “ylone”) are currently the most popular subclass of synthetic stimulants. Leading up to its federal scheduling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 21 publications
4
33
0
Order By: Relevance
“…Since that time, it has been detected in 17 countries across Europe, but it was only during 2019–2020 that there has been a marked increase in the availability of eutylone in the European Union, the U.S., New Zealand, and other parts of the world . In the U.S., eutylone was the most commonly reported cathinone in drug seizures and biological samples during 2019, a trend that has continued through 2020. These data demonstrate that the availability and misuse of eutylone are increasing worldwide.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Since that time, it has been detected in 17 countries across Europe, but it was only during 2019–2020 that there has been a marked increase in the availability of eutylone in the European Union, the U.S., New Zealand, and other parts of the world . In the U.S., eutylone was the most commonly reported cathinone in drug seizures and biological samples during 2019, a trend that has continued through 2020. These data demonstrate that the availability and misuse of eutylone are increasing worldwide.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, 1-(1,3-benzodioxol-5-yl)-2-(ethylamino)­butan-1-one, also known as “bk-EBDB” or “eutylone”, has emerged on recreational drug markets in the United States (U.S.) and elsewhere . From a chemical structure perspective, eutylone is a methylone analog that contains ethyl groups at both the α-carbon and amine positions (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…and 1.2-11,000 ng/ml in blood samples of post-mortem cases. 23 Krotulski et al also found evidence of use of multiple drugs besides eutylone, like cocaine, fentanyl and methamphetamine. 23 The metabolites detected in authentic samples are also shown in Although phase II metabolites are not included in this report, the concentrations of 4-hydroxy-3-methoxy and 3-hydroxy-4-methoxy metabolites could be assumed to increase after glucuronidase and sulfatase hydrolysis, based on some published studies.…”
Section: Analysis Results Of Authentic Samplesmentioning
confidence: 99%
“…N-Ethylpentylone concentrations in postmortem blood ranged from 7 to 170 ng/mL in Brazilian cases [6] and from 12 to 1200 ng/mL in USA [35,36]. Lee et al [32] reported seven postmortem cases with ethylone detected in blood, ranging from 38 to 2572 ng/mL and Krotulski et al [37] reported 22 postmortem cases involving eutylone, with blood levels ranging from 1.2 to 11,000 ng/mL and two urine samples (60 and > 10,000 ng/mL). To the best of our knowledge, this is the first study that uses a QuEChERS method for the analysis of a large number of analytes that included 25R-NBOMe and 25R-NBOH family compounds in blood and urine.…”
Section: Discussionmentioning
confidence: 99%